U–Pb Zircon geochronology of the Cambro-Ordovician metagranites and metavolcanic rocks of central and NW Iberia - Talavera, Cristina; Montero, P.; Bea, F.; Gonzalez Lodeiro, F.; Whitehouse, M (Springer, 2013)
New U–Pb zircon data from metagranites and metavolcanic rocks of the Schist-Graywacke Complex Domain and the Schistose Domain of Galicia Tras-os-Montes Zone from central and NW Iberia contribute to constrain the timing of the Cambro-Ordovician magmatism from Central Iberian and Galicia Tras-os-Montes Zones which occurred between 498 and 462 Ma. The crystallization ages of the metagranites and metavolcanic rocks from the northern Schist-Graywacke Complex Domain are as follows: (a) in west Salamanca, 489 ± 5 Ma for Vitigudino, 486 ± 6 Ma for Fermoselle and 471 ± 7 Ma for Ledesma; (b) in northern Gredos, 498 ± 4 Ma for Castellanos, 492 ± 4 Ma for San Pelayo and 488 ± 3 Ma for Bercimuelle; (c) in Guadarrama, 490 ± 5 Ma for La Estacion I, 489 ± 9 Ma for La Canada, 484 ± 6 Ma for Vegas de Matute (leucocratic), 483 ± 6 Ma for El Cardoso, 482 ± 8 Ma for La Morcuera, 481 ± 9 Ma for Buitrago de Lozoya, 478 ± 7 Ma for La Hoya, 476 ± 5 Ma for Vegas de Matute (melanocratic), 475 ± 5 Ma for Riaza, 473 ± 8 Ma for La Estacion II and 462 ± 11 Ma for La Berzosa; and (d) in Toledo, 489 ± 7 Ma for Mohares and 480 ± 8 Ma for Polan. The crystallization ages of the metagranites from the Schistose Domain of Galicia Tras-os-Montes Zone are 497 ± 6 Ma for Laxe, 486 ± 8 Ma for San Mamede, 482 ± 7 Ma for Bangueses, 481 ± 5 Ma for Noia, 480 ± 10 for Rial de Sabucedo, 476 ± 9 Ma for Vilanova, 475 ± 6 Ma for Pontevedra, 470 ± 6 Ma for Cherpa and 462 ± 8 Ma for Bande.This magmatism is characterized by an average isotopic composition of (87Sr/86Sr)485Ma ≈ 0.712, (eNd)485Ma ≈ -4.1 and (TDM) ≈ 1.62 Ga, and a high zircon inheritance, composed of Ediacaran–Early Cambrian (65 %) and, to a lesser extent, Cryogenian, Tonian, Mesoproterozoic, Orosirian and Archean pre-magmatic cores. Combining our geochronological and isotopic data with others of similar rocks from the European Variscan Belt, it may be deduced that Cambro-Ordovician magmas from this belt were mainly generated by partial melting of Ediacaran–Early Cambrian igneous rocks.